2009
DOI: 10.1186/1757-1626-2-9406
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fungal sinusitis leading to disastrous cerebral aspergillosis: a case report

Abstract: Cerebral angioinvasion is a fatal complication of disseminated aspergillosis and has been rarely described in diabetic population in the absence of ketoacidosis. We present a case of invasive fungal sinusitis in a 79 year old diabetic man who presented with chronic frontal headaches. Despite appropriate medical and surgical treatment, the disease progressed and the patient eventually succumbed to a fatal ruptured mycotic aneurysm. We emphasize that clinicians should consider this in the differential diagnoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Aspergillus species are usually isolated from these cases. 4,5 Delay in diagnosis is a typical finding across the literature; moreover, the ideal management approach is controversial and is subject to several influencing factors such as the nature of the disease, the degree of tissue invasion, and patient comorbidities. 6 In view of the paucity of reports on CGIFS, we present 7 cases of patients diagnosed with the disease and we review the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus species are usually isolated from these cases. 4,5 Delay in diagnosis is a typical finding across the literature; moreover, the ideal management approach is controversial and is subject to several influencing factors such as the nature of the disease, the degree of tissue invasion, and patient comorbidities. 6 In view of the paucity of reports on CGIFS, we present 7 cases of patients diagnosed with the disease and we review the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that invasive cerebral aspergillosis is a complicated and quick progressive disease that cause high mortality rate up to hundred percent even with effective management. 1 Aspergillus species can invade cerebral vessels leading to different pathologies including infarction or hemorrhage leading to progressive inflammation.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Acute invasive fungal sinusitis results from a rapid spread of fungi through vascular invasion into the orbit Invasive aspergillus sinusitis of this patient showed invasive complications that rarely happened in other populations based on previous researches of meningitis as seen on time line Table 1, orbital involvement, skull base erosion with intracranial extension, and infratemporal fossa extension multiple vasculitis with diffuse brain edema and hydrocephalous. 1,2 The likely pathogenesis of cerebral infarction is by direct angioinvasion and less likely compression by oedema.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation